Sclerosing angiomatoid nodular transformation of the accessory spleen: A case report and review of literature. Issue 26 (June 2018) - Niu, Miao; Liu, Ailian; Wu, Jingjun; Zhang, Qinhe; Liu, Jinghong
Abstract: Rationale: Sclerosing angiomatoid nodular transformation (SANT) is a rare case which usually occurs in spleen, but our case occurs in accessory spleen. Patient concerns: We reported a case of a 27 year old man who was identified with an isodense mass in the left abdominal cavity by ultrasonicphysical examination without symptoms. Blood routine and tumor markers (alpha fetal protein, carcinoembryonic antigen, CA19-9, CA125) were normal. Diagnoses: The tumor was firstly diagnosed as left abdominal mass and its origin was considered as small intestinal by the radiologist. The pathological diagnosis was the sclerosing angiomatoid nodular transformation (SANT) of the accessory spleen. Interventions: Laparoscopic splenectomy is a more reliable method for the treatment of SANT. Outcomes: Non-enhanced CT showed iso-intensity lesion of the accessory spleen, and enhanced CT showed progressive enhancement. According to the above characteristics, we should consider the diagnosis of spleen SANT. We reviewed some literatures to summarize the characteristics of SANT.